Legal Risk and Impact of Fake Review in Online Commerce (Comparative Study Indonesia and Uzbekistan) - Prastyanti, Rina Arum; Sobirov, Bobur (Westscience Press, 2025)
This study aims to outline the legal risks and consequences of fake reviews in online commerce as they relate to Indonesian and Uzbek laws. The next goal is to learn about Indonesia's legal reconstruction laws that shield online shoppers from fraudulent reviews. This study employs a legal research methodology that looks at pertinent legal provisions to what is actually taking place in society. Primary data are those that can be used as research materials. Information such as Uzbek and Indonesian laws and regulations that control the legal risks and effects of fraudulent reviews on internet sales, as well as secondary data that links the effects and The potential legal ramifications of fraudulent online reviews in Uzbekistan and Indonesia. This study approach reviews Uzbek and Indonesian legal guidelines and policies using statutory techniques. Because the research's findings are presented in a descriptive-analytical way, this type of study is also known as descriptive-analytical research.